Atopic dermatitis: Is innate or adaptive immunity in control? A clinical perspective - Ong, Peck Y. (Frontiers in Immunology, 2022)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with barrier defects and immune dysregulations. The pathogenesis of AD involves the physical barrier as well as epithelial cells, which are considered a vital part of the innate immunity of the skin. The importance of filaggrin mutations in the pathogenesis of AD has also been well-established with reproducible results around the world in multiple studies and ethnic groups. This protein plays an important role in skin barrier functions and further reaffirms barrier defects as one of the primary causes of AD. The main epithelial cells, keratinocytes, function as a major sentinel for the skin in detecting danger signals or microbial pathogens, and trigger downstream immune responses. In AD, these cells express TSLP, IL-33 and IL-25, which lead to downstream systemic production of type 2 cytokines. In spite of major advances in our understanding of the innate immunity of AD, recent success in the systemic therapeutics of AD have focused on targeting the products of the adaptive immunity, particularly cytokines produced by T cells. In addition to type 2 cytokines, type 17 cytokines have also been implicated in the pathogenesis of AD. The current review examines the implications of these cytokines in AD from clinical perspectives.